Multiple correspondence analysis dalam pemetaan persepsi berdasarkan adjusted inertia - Safitri, Yolanda Rahmi (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to conduct perception mapping of five mobile operators (Telkomsel, XL Aciata, Smartfren, IM3, and Tri) based on the categories of tarrifs, company services, product quality, promotions, and consumer knowledge regarding the respective operators. The perception mapping was carried out using the Multiple Correspondence Analysis (MCA) method with the Adjusted Inertia approach, which provides more realistic inertia estimates and enables a more objective interpretation of the relationships among variables. The mapping was performed using column profile coordinates (categpries) and row profile coordinates (respondents). The analysis results indicate that Tri and Telkomsel are competitive in terms of company service, while IM3 is the most widely used operator based on the influencing categories.Keywords: Multivariate Analysis, Multiple Correspondence Analysis, Perceptual Mapping, Adjusted Inertia